Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment

By introducing spinel phase and layered structure into the positive electrode active material of lithium-ion secondary batteries, the problems of insufficient spinel structure and low conductivity of layered structure are solved, and a positive electrode active material with high conductivity and high rate performance is achieved, which is suitable for batteries with high capacity and high rate performance requirements.

CN119725419AActive Publication Date: 2025-03-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311279322.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The spinel structure positive electrode active material of existing lithium-ion secondary batteries has a low capacity and is difficult to meet the high capacity requirements. The layered structure positive electrode active material has a low conductivity and average rate performance, making it difficult to meet the high rate performance requirements.

Method used

The positive electrode active material with the chemical formula of LiaNibMncMdO2 is adopted, and its microstructure includes both a layered structure and a spinel phase. The layered structure is introduced through the spinel phase to improve the stability and conductivity of the material, and to a certain extent make up for the shortcomings of insufficient spinel material capacity.

Benefits of technology

It realizes the high conductivity and high rate performance of the positive electrode active material, and has the advantages of layered structure and spinel structure, and is suitable for batteries with high capacity and high rate performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725419A_ABST
    Figure CN119725419A_ABST
Patent Text Reader

Abstract

The invention relates to a positive active material and a preparation method thereof, a positive pole piece, a battery and electric equipment. The chemical formula of the positive electrode active material is LiaNibMncMdO2, a is greater than or equal to 1 and less than or equal to 1.05, b is greater than or equal to 0.22 and less than or equal to 0.5, c is greater than or equal to 0.47 and less than or equal to 0.75, d is greater than or equal to 0.01 and less than or equal to 0.03, and M comprises at least one of Mg, Nb, Cr, Ce, Fe, La, Ta, Al, V, Ti, Zr, Sn, Mo or Co; the XRD spectrum of the material comprises a first main diffraction peak and a second main diffraction peak; the diffraction angle of the first main diffraction peak is 16-19 degrees; and the diffraction angle of the second main diffraction peak is 42-45 degrees. The material has the advantages of a positive electrode active material with a layered structure and the advantages of a positive electrode active material with a spinel structure, and the rate capability of the positive electrode active material is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery, and an electrical device. Background Art

[0002] In recent years, with the development of lithium-ion secondary battery technology, lithium-ion secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion secondary batteries have made great progress, higher requirements have been put forward for their rate performance. Summary of the invention

[0003] The purpose of the present application is to provide a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery, and an electrical device.

[0004] The embodiment of the present application is implemented as follows:

[0005] In a first aspect, the present invention provides a positive electrode active material, the chemical formula of the positive electrode active material is: Li a Ni b Mn c M d O2, wherein 1≤a≤1.05, 0.22≤b≤0.5, 0.47≤c≤0.75, 0.01≤d≤0.03, and M includes at least one of Mg, Nb, Cr, Ce, Fe, La, Ta, Al, V, Ti, Zr, Sn, Mo or Co; the XRD spectrum of the positive electrode active material includes a first main diffraction peak and a second main diffraction peak; the diffraction angle of the first main diffraction peak is 16°~19°; the diffraction angle of the second main diffraction peak is 42°~45°.

[0006] The study found that compared with layered positive electrode active materials, spinel positive electrode active materials have a lower specific capacity, and it is difficult to meet the needs of high-capacity batteries using a single spinel positive electrode active material; and layered positive electrode active materials have lower electrical conductivity and average rate performance than spinel positive electrode active materials, and therefore are difficult to meet the requirements of batteries with high rate performance.

[0007] In the technical solution of the present application, the positive electrode active material includes the above-mentioned first main diffraction peak and the second main diffraction peak, and the material microstructure includes both a layered structure and a spinel phase. In this positive electrode active material, a spinel phase is introduced into the layered structure, which improves the stability of the layered structure, and the three-dimensional lithium ion diffusion channel of the spinel phase improves the electrical conductivity of the layered material; at the same time, by introducing a layered structure into the spinel phase, the disadvantage of insufficient capacity of the spinel material is compensated to a certain extent. The positive electrode active material of this structure of the present application has both the advantages of a positive electrode active material with a layered structure and the advantages of a positive electrode active material with a spinel structure, which is beneficial to improving the electrical conductivity of the material, thereby helping to improve the rate performance of the positive electrode active material.

[0008] In some optional embodiments, the ratio of the intensity of the first main diffraction peak to the intensity of the second main diffraction peak is 0.8 to 2.0. Alternatively, the ratio of the intensity of the first main diffraction peak to the intensity of the second main diffraction peak is 0.8 to 1.0.

[0009] In the above technical solution, the ratio of the intensity of the first main diffraction peak to the intensity of the second main diffraction peak is 0.8 to 2.0, which is further beneficial to improving the conductivity of the positive electrode active material and further beneficial to improving the rate performance of the positive electrode active material.

[0010] In some optional embodiments, the specific surface area of ​​the positive electrode active material after washing is less than 8 m 2 / g; Optionally, the specific surface area of ​​the positive electrode active material after washing is greater than 2m 2 / g and less than 8m 2 / g.

[0011] In the above technical scheme, the specific surface area of ​​the positive electrode active material after washing is within the above range, which is beneficial to the reaction of the electrolyte on the surface of the positive electrode active material, thereby being beneficial to the electrochemical performance of the battery; at the same time, the specific surface area of ​​the positive electrode active material after washing is within the above range, which is beneficial to the kinetic behavior of reversible embedding and de-embedding of lithium ions in the positive electrode active material.

[0012] In some optional embodiments, the dislocation density of the positive electrode active material is 1.0*10 13 ~2.5*10 13 ; Optionally, the dislocation density of the positive electrode active material is 1.0*10 13 ~2.0*10 13 .

[0013] In the above technical solution, the dislocation density of the positive electrode active material is within the above range, which is beneficial to reducing the stacking faults of the positive electrode active material. The dislocation density reflects the number of line defects in the material. Inappropriate stacking faults will cause changes in the local Coulomb repulsion between Li-Li and Li-TM cations, thereby causing the voltage decay of the material. Reasonable dislocation density can reduce voltage decay and improve the cycle.

[0014] In some optional embodiments, the micro stress of the positive electrode active material is less than or equal to 1.2%. Optionally, the micro stress of the positive electrode active material is 0.1% to 0.5%.

[0015] In the above technical solution, the microstress of the positive electrode active material is within the above range, which is beneficial to reduce the stress accumulation of the positive electrode active material particles during the charge and discharge cycle, improve the secondary ball breakage phenomenon caused by excessive stress, and thus help improve the stability of the material.

[0016] In some optional embodiments, the material diameter distance of the positive electrode active material is greater than 1.2; optionally, the material diameter distance of the positive electrode active material is greater than 1.2 and less than 1.5.

[0017] In the above technical solution, the material span of the positive electrode active material is within the above range, which is beneficial to improving the space utilization of the positive electrode active material and improving the compaction density and gram capacity.

[0018] In a second aspect, the present application provides a method for preparing the positive electrode active material provided in the first aspect, comprising:

[0019] A mixture of a hydroxide precursor and a lithium salt is sintered; the total metal in the hydroxide precursor is Me, and Me includes nickel, manganese and M.

[0020] In the above technical solution, the mixture of hydroxide precursor and lithium salt is sintered, and a layered structure is introduced into the spinel phase, which makes up for the shortcoming of insufficient capacity of the spinel material to a certain extent. It is beneficial to improve the conductivity of the positive electrode active material and improve the rate performance of the positive electrode active material.

[0021] In some optional embodiments, the sintering includes: sintering the mixture at 400° C. to 480° C. for 25 h to 75 h.

[0022] In the above technical scheme, a positive electrode active material containing both a spinel phase and a layered structure is prepared by sintering at a low temperature of 400°C to 480°C for 25h to 75h. The introduction of the spinel phase improves the stability of the layered structure, and the three-dimensional lithium ion diffusion channel improves the electrical conductivity of the layered material; and the layered structure makes up for the disadvantage of insufficient capacity of the spinel material to a certain extent.

[0023] In some optional embodiments, the molar ratio of the Li element of the lithium salt to the Me element of the hydroxide precursor is 1.0 to 1.05.

[0024] In the above technical solution, the molar ratio of the Li element of the lithium salt to the Me element of the hydroxide precursor is 1.0 to 1.05. Within this range, it is further beneficial to improve the conductivity of the positive electrode active material and further beneficial to improve the rate performance of the positive electrode active material.

[0025] In some optional embodiments, the mixture is sintered at 400° C. to 480° C. for 25 h to 75 h, comprising:

[0026] The temperature is raised from room temperature to 400°C to 480°C at a heating rate of 1°C / min to 3°C / min and sintered for 25h to 75h.

[0027] In the above technical solution, the above heating rate is advantageous for obtaining a positive electrode active material containing both a spinel phase and a layered structure.

[0028] In some alternative embodiments, the sintering atmosphere is air.

[0029] In the above technical solution, the above-mentioned air atmosphere sintering is adopted, which is conducive to obtaining a positive electrode active material containing both a spinel phase and a layered structure.

[0030] In some optional embodiments, the method further comprises:

[0031] Washing the sintered material with water;

[0032] The mass ratio of water to fuel is (15-30):1; optionally, the water washing time is 15min-30min.

[0033] In the above technical solution, the sintered material is washed with water to remove residual lithium, which is beneficial for obtaining positive electrode active materials with less impurities.

[0034] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect; or the positive electrode plate comprises the positive electrode active material prepared by the preparation method of the positive electrode active material provided in the second aspect.

[0035] In the above technical solution, the electrode sheet can improve rate performance by setting the positive electrode active material provided by the first aspect or the positive electrode active material prepared by the preparation method of the positive electrode active material provided by the second aspect.

[0036] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode plate provided in the second aspect.

[0037] In the above technical solution, the battery is provided with the positive electrode plate provided by the third aspect, which is beneficial to improving the rate performance.

[0038] In a fifth aspect, an embodiment of the present application provides an electrical device, which includes the battery provided in the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 A schematic diagram of the structure of a vehicle provided in some embodiments of the present application;

[0041] Figure 2 An exploded view of a battery provided for some embodiments of the present application;

[0042] Figure 3 for Figure 2 An exploded view of a battery cell is shown;

[0043] Figure 4 A schematic diagram of a partial structure of an electrode assembly provided in some embodiments of the present application;

[0044] Figure 5 A schematic diagram of a partial structure of a positive electrode sheet provided in some embodiments of the present application;

[0045] Figure 6 The charge and discharge curves are provided for comparative examples and some embodiments of the present application.

[0046] icon:

[0047] Vehicles 1000;

[0048] Battery 100; Controller 200; Motor 300;

[0049] Box body 10; first part 11; second part 12; accommodating space 13;

[0050] Battery cell 20; housing 21; electrode assembly 22; electrode terminal 23; pressure relief structure 24;

[0051] Shell 211; cover 212; positive electrode sheet 221; negative electrode sheet 222; isolation film 223;

[0052] Positive electrode current collector 2211; Positive electrode active material layer 2212;

[0053] Negative electrode current collector 2221 ; negative electrode active material layer 2222 . DETAILED DESCRIPTION

[0054] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0056] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0057] In the description of the embodiments of the present application, the orientations or positional relationships indicated by the technical terms "inside" and "outside" are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.

[0058] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral one; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present application can be understood according to specific circumstances.

[0059] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0060] In the embodiments of the present application, the same reference numerals represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments. It should be understood that the heights, lengths, widths, and other dimensions of the various components in the embodiments of the present application shown in the drawings, as well as the overall heights, lengths, widths, and other dimensions of the integrated device are only exemplary descriptions and should not constitute any limitation to the present application.

[0061] The study found that compared with layered positive electrode active materials, spinel positive electrode active materials have a lower specific capacity, and it is difficult to meet the needs of high-capacity batteries using a single spinel positive electrode active material; and layered positive electrode active materials have lower electrical conductivity and average rate performance than spinel positive electrode active materials, and therefore are difficult to meet the requirements of batteries with high rate performance.

[0062] The present invention provides a positive electrode active material, the chemical formula of the positive electrode active material is: Li a Ni b Mn c M d O2, wherein 1≤a≤1.05, 0.22≤b≤0.5, 0.47≤c≤0.75, 0.01≤d≤0.03, and M includes at least one of Mg, Nb, Cr, Ce, Fe, La, Ta, Al, V, Ti, Zr, Sn, Mo or Co; the XRD spectrum of the positive electrode active material includes a first main diffraction peak and a second main diffraction peak; the diffraction angle of the first main diffraction peak is 16°~19°; the diffraction angle of the second main diffraction peak is 42°~45°.

[0063] In the above technical solution, the positive electrode active material includes the above-mentioned first main diffraction peak and the second main diffraction peak, and the material microstructure includes both a layered structure and a spinel phase. In this positive electrode active material, a spinel phase is introduced into the layered structure, which improves the stability of the layered structure, and the three-dimensional lithium ion diffusion channel of the spinel phase improves the electrical conductivity of the layered material; at the same time, by introducing a layered structure into the spinel phase, the disadvantage of insufficient capacity of the spinel material is compensated to a certain extent. The positive electrode active material of this structure of the present application has both the advantages of a positive electrode active material with a layered structure and the advantages of a positive electrode active material with a spinel structure, which is beneficial to improving the electrical conductivity of the positive electrode active material and improving the rate performance of the positive electrode active material.

[0064] The positive electrode sheet provided in the present application includes the positive electrode active material mentioned above.

[0065] The pole piece can improve rate performance by arranging the aforementioned positive electrode active material.

[0066] The battery provided in the present application includes the aforementioned positive electrode plate.

[0067] The battery is advantageously improved in rate performance by providing the positive electrode plate provided by the third aspect.

[0068] An embodiment of the present application provides an electrical device, comprising the aforementioned battery.

[0069] See also Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.

[0070] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0071] In the present application, a battery 100 refers to a single physical module including one or more battery cells 20 to provide voltage and capacity. The battery 100 generally includes a housing 10 for encapsulating one or more battery cells 20. The housing 10 can prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.

[0072] See also Figure 2 , Figure 2The exploded diagram of the battery 100 provided in some embodiments of the present application, the battery 100 may include a box body 10 and a battery cell 20, and the battery cell 20 is accommodated in the box body 10. Among them, the box body 10 is used to accommodate the battery cell 20, and the box body 10 can be a variety of structures. In some embodiments, the box body 10 may include a first part 11 and a second part 12, the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a receiving space 13 for accommodating the battery cell 20. The second part 12 may be a hollow structure with one end open, the first part 11 is a plate-like structure, and the first part 11 covers the open side of the second part 12 to form a box body 10 with a receiving space 13; the first part 11 and the second part 12 may also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12 to form a box body 10 with a receiving space 13. Of course, the first part 11 and the second part 12 may be a variety of shapes, such as a cylinder, a cuboid, etc.

[0073] In the battery 100, there can be one or more battery cells 20. If there are more than one battery cell 20, the multiple battery cells 20 can be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 can be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10. Alternatively, multiple battery cells 20 can be connected in series, in parallel, or in a mixed connection to form a module, and the multiple modules are then connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery 100 may also include other structures. For example, the multiple battery cells 20 can be electrically connected through a busbar component to achieve parallel, series, or mixed connection of the multiple battery cells 20.

[0074] See also Figure 3 , Figure 3 for Figure 2 The exploded view of the battery cell 20 is shown. The battery cell 20 refers to the smallest unit constituting the battery 100. The battery cell 20 may include a housing 21, an electrode assembly 22 and an electrolyte, and the electrode assembly 22 and the electrolyte are both contained in the housing 21.

[0075] The housing 21 may include a shell 211 and a cover 212. The shell 211 is a component used to cooperate with the cover 212 to form an internal sealed space of the battery cell 20, wherein the formed sealed space can be used to accommodate the electrode assembly 22, electrolyte and other components. The cover 212 refers to a component that covers the opening of the shell 211 to isolate the internal environment of the battery cell 20 from the external environment. The shape of the cover 212 can be adapted to the shape of the shell 211 to cooperate with the shell 211, and the cover 212 may also be provided with functional components such as electrode terminals 23 and pressure relief structures 24. A sealing ring may be configured between the opening of the shell 211 and the cover 212 to achieve sealing between the shell 211 and the cover 212.

[0076] The shell 211 and the cover 212 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shapes of the shell 211 and the cover 212 can be determined according to the specific shape and size of the electrode assembly 22. The shell 211 and the cover 212 can be made of various materials, such as but not limited to metals such as copper, iron, aluminum, stainless steel, and aluminum alloy. The sealing ring can be made of various materials, such as but not limited to PP (polypropylene), PC (polycarbonate), PET (polyethylene terephthalate) and other materials that are resistant to electrolyte corrosion, high toughness and fatigue resistance. A coating can be formed on the outer surface of the shell 211, and the material of the coating can be various, such as but not limited to corrosion-resistant materials such as Ni and Cr.

[0077] See also Figure 4 The electrode assembly 22 may be composed of a positive electrode sheet 221, a negative electrode sheet 222, and a separator 223. The separator 223 is located between the positive electrode sheet 221 and the negative electrode sheet 222 to play a role of isolation. The electrode assembly 22 may be a winding structure or a laminated structure, but the embodiments of the present application are not limited thereto.

[0078] See also Figure 5 The negative electrode sheet 222 includes a negative electrode current collector 2221 and a negative electrode active material layer 2222. The negative electrode current collector 2221 may be made of copper, and the negative electrode active material layer 2222 includes a negative electrode active material. The negative electrode active material includes at least one of graphite, silicon, silicon alloy, or tin alloy.

[0079] Please continue to see Figure 5 The positive electrode sheet 221 includes a positive electrode current collector 2211 and a positive electrode active material layer 2212. Taking the lithium-ion battery cell 20 as an example, the material of the positive electrode current collector 2211 can be aluminum. The positive electrode active material layer 2212 includes a positive electrode active material.

[0080] In some embodiments of the present application, the chemical formula of the positive electrode active material is: Li a Nib Mn c M d O2, wherein 1≤a≤1.05, 0.22≤b≤0.5, 0.47≤c≤0.75, 0.01≤d≤0.03, and M includes at least one of Mg, Nb, Cr, Ce, Fe, La, Ta, Al, V, Ti, Zr, Sn, Mo or Co; the XRD spectrum of the positive electrode active material includes a first main diffraction peak and a second main diffraction peak; the diffraction angle of the first main diffraction peak is 16°~19°; the diffraction angle of the second main diffraction peak is 42°~45°.

[0081] Diffraction peaks refer to the diffraction peaks produced by the reflection of X-rays at different angles by the crystal planes of the sample crystal structure in the X-ray diffraction test. The diffraction angle refers to the angle between the X-rays and the crystal planes.

[0082] In the above technical solution, the positive electrode active material includes the above-mentioned first main diffraction peak and the second main diffraction peak, and the material microstructure includes both a layered structure and a spinel phase. In this positive electrode active material, a spinel phase is introduced into the layered structure, which improves the stability of the layered structure, and the three-dimensional lithium ion diffusion channel of the spinel phase improves the electrical conductivity of the layered material; at the same time, by introducing a layered structure into the spinel phase, the disadvantage of insufficient capacity of the spinel material is compensated to a certain extent. The positive electrode active material of this structure of the present application has both the advantages of a positive electrode active material with a layered structure and the advantages of a positive electrode active material with a spinel structure, which is beneficial to improving the electrical conductivity of the positive electrode active material and improving the rate performance of the positive electrode active material.

[0083] It should be noted that the microstructure of the positive electrode active material can be observed through a transmission electron microscope (TEM). Under the transmission electron microscope, it can be seen that the positive electrode active material includes both a layered structure and a spinel phase.

[0084] Further, illustratively, in some embodiments of the present application, the chemical formula of the positive electrode active material is: LiNi 0.5 Mn 0.5 O2、LiNi 0.25 Mn 0.5 O2、LiNi 0.5 Mn 0.75 O2、LiNi 0.5 Mn 0.5 Mg 0.01 O2、LiNi 0.5 Mn 0.5 Nb 0.01 O2、Li 1.05 Ni 0.25 Mn 0.75 Cr 0.03 O2、Li 1.02 Ni0.3 Mn 0.6 Ce 0.03 O2、Li 1.03 Ni 0.35 Mn 0.65 Fe 0.02 O2、Li 1.04 Ni 0.45 Mn 0.55 Ta 0.01 O2、Li 1.01 Ni 0.26 Mn 0.56 Al 0.03 O2、Li 1.01 Ni 0.26 Mn 0.56 V 0.03 O2、Li 1.05 Ni 0.25 Mn 0.75 Ti 0.03 O2、LiNi 0.5 Mn 0.5 Zr 0.01 Sn 0.02 O2 or Li 1.05 Ni 0.25 Mn 0.75 Mo 0.03 Co 0.01 O2.

[0085] It should be noted that when the above M is selected from two or more elements, the content of each element satisfies 0.01≤d≤0.03.

[0086] For example, in some embodiments of the present application, the chemical formula of the positive electrode active material is: LiNi 0.5 Mn 0.5 Zr 0.01 Sn 0.02 O2、Li 1.05 Ni 0.25 Mn 0.75 Mo 0.03 Co 0.01 O2 or LiNi 0.5 Mn 0.5 Nb 0.01 Ti 0.01 Zr 0.01 O2.

[0087] It should be further explained that the battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0088] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0089] Further optionally, in some embodiments of the present application, the diffraction angle of the first main diffraction peak is 17° to 18°.

[0090] Illustratively, in some embodiments of the present application, the diffraction angle of the first main diffraction peak is 16°, 17°, 18°, 19° or a range between any two of the aforementioned values.

[0091] Furthermore, in some embodiments of the present application, the diffraction angle of the second main diffraction peak is 43° to 44°.

[0092] Illustratively, in some embodiments of the present application, the diffraction angle of the second main diffraction peak is 42°, 43°, 44°, 45° or a range between any two of the aforementioned values.

[0093] Furthermore, in some embodiments of the present application, the ratio of the intensity of the first main diffraction peak to the intensity of the second main diffraction peak is 0.8 to 2.0.

[0094] The intensity of the diffraction peak indicates the degree of crystallinity. The greater the intensity of the diffraction peak, the better the degree of crystallinity.

[0095] In some embodiments of the present application, the intensity of the diffraction peak can be tested with reference to the test method: JSK 0131-1996.

[0096] In the above technical solution, the ratio of the intensity of the first main diffraction peak to the intensity of the second main diffraction peak is 0.8 to 2.0, which is further beneficial to improving the conductivity of the positive electrode active material and further beneficial to improving the rate performance of the positive electrode active material.

[0097] Illustratively, in some embodiments of the present application, the ratio of the intensity of the first main diffraction peak to the intensity of the second main diffraction peak is 0.81, 0.83, 0.85, 0.88, 1.90, 1.92, 1.95, 2.0 or a range between any two of the aforementioned values.

[0098] Further optionally, in some embodiments of the present application, the ratio of the intensity of the first main diffraction peak to the intensity of the second main diffraction peak is 0.81 to 1.99.

[0099] Further, in some embodiments of the present application, the specific surface area of ​​the positive electrode active material after washing is less than 8m 2 / g.

[0100] Further optionally, in some embodiments of the present application, the specific surface area of ​​the positive electrode active material after washing is greater than 2 m 2 / g and less than 8m 2 / g.

[0101] In the above technical scheme, the specific surface area of ​​the positive electrode active material after washing is within the above range, which is beneficial to the reaction of the electrolyte on the surface of the positive electrode active material, thereby being beneficial to the electrochemical performance of the battery; at the same time, the specific surface area of ​​the positive electrode active material after washing is within the above range, which is beneficial to the kinetic behavior of reversible embedding and de-embedding of lithium ions in the positive electrode active material.

[0102] For example, in some embodiments of the present application, the specific surface area of ​​the positive electrode active material after washing is 7.5 m 2 / g, 6m 2 / g, 5m 2 / g, 4m 2 / g, 3m 2 / g, 2m 2 / g, 1m 2 / g or the range between any two of the above values.

[0103] Further, in some embodiments of the present application, the dislocation density (β) of the positive electrode active material is 1.0*10 13 ~2.5*10 13 .

[0104] In the above technical solution, the dislocation density of the positive electrode active material is within the above range, which is beneficial to reduce stacking faults and improve voltage decay during the cycle process.

[0105] Further optionally, in some embodiments of the present application, the dislocation density of the positive electrode active material is 1.1*10 13 ~2.4*10 13 .

[0106] For example, in some embodiments of the present application, the dislocation density of the positive electrode active material is 1.1*10 13 , 1.5*10 13 , 1.8*10 13 , 2.0*10 13 , 2.2*10 13 , 2.3*1013 , 2.4*10 13 , 2.5*10 13 Or the range between any two of the above values.

[0107] Further, in some embodiments of the present application, the dislocation density testing method is:

[0108] The dislocation density of the positive electrode active material was tested using XRD diffraction patterns.

[0109] Dislocation density β = (1 / D) 2 ×10 16 , where D = K λ / Bcosθ, K=0.9, λ=1.5406, B is the half-height width of the crystal plane of the positive electrode active material (hkl) in the XRD diffraction pattern, and θ is the diffraction angle.

[0110] Furthermore, in some embodiments of the present application, the micro stress of the positive electrode active material is less than or equal to 1.2%.

[0111] In the above technical solution, the microstress of the positive electrode active material is within the above range, which is beneficial to reduce the stress accumulation of the positive electrode active material particles during the charge and discharge cycle, improve the secondary ball breakage phenomenon caused by excessive stress, and thus help improve the stability of the material.

[0112] Further optionally, in some embodiments of the present application, the micro stress of the positive electrode active material is 0.1% to 0.5%.

[0113] Illustratively, in some embodiments of the present application, the micro stress of the positive electrode active material is 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or a range between any two of the foregoing values.

[0114] Further, in some embodiments of the present application, the micro stress detection method:

[0115] XRD diffraction patterns were used to test the micro stress of the positive electrode active material.

[0116] Micro stress = (βhkl × Cosθhkl) / (4sinθhkl), where θhkl is the diffraction angle of the positive electrode material (hkl) crystal plane in the XRD diffraction pattern, and βhkl is the half-height width of the positive electrode material (hkl) crystal plane in the XRD diffraction pattern.

[0117] Furthermore, in some embodiments of the present application, the material diameter distance of the positive electrode active material is greater than 1.2.

[0118] In the above technical solution, the material span of the positive electrode active material is within the above range, which is beneficial to improving the space utilization of the positive electrode active material and improving the compaction density and gram capacity.

[0119] Further optionally, in some embodiments of the present application, the material diameter distance of the positive electrode active material is greater than 1.2 and less than 1.5.

[0120] Illustratively, in some embodiments of the present application, the material span of the positive electrode active material is 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or a range between any two of the foregoing values.

[0121] Further, in some embodiments of the present application, the material span is measured by referring to GB / T19077-2016 / ISO 13320:2009 particle size distribution laser diffraction method, using Malvern 3000 equipment for measurement, Span = (D v90 -D v10 ) / D v50 .

[0122] Above D V50 It means: when the positive electrode active material particles are added up from small to large, and when the accumulated volume accounts for 50% of the total volume, the particle size of the positive electrode active material particles is less than a certain value, then the value is D v50 The value of .

[0123] Above D v10 It means: when the positive electrode active material particles are added up from small to large, and when the accumulated volume accounts for 10% of the total volume, the particle size of the positive electrode active material particles is less than a certain value, then the value is D v10 The value of .

[0124] Above D v90 It means: when the positive electrode active material particles are added up from small to large, and when the accumulated volume accounts for 90% of the total volume, the particle size of the positive electrode active material particles is less than a certain value, then the value is D v90 The value of .

[0125] Above D v10 , D v50 or D v90 Refer to GB / T 19077-2016 / ISO 13320:2009 particle size distribution laser diffraction method, and use Malvern 3000 equipment for measurement.

[0126] Some embodiments of the present application provide a method for preparing a positive electrode active material, comprising: sintering a mixture of a hydroxide precursor and a lithium salt; the total metal in the hydroxide precursor is Me, and Me includes nickel, manganese and M.

[0127] In the above technical solution, the mixture of hydroxide precursor and lithium salt is sintered, and a layered structure is introduced into the spinel phase, which makes up for the shortcoming of insufficient capacity of the spinel material to a certain extent. It is beneficial to improve the conductivity of the positive electrode active material and improve the rate performance of the positive electrode active material.

[0128] Furthermore, in some embodiments of the present application, the sintering includes: sintering the mixture at 400° C. to 480° C. for 25 h to 75 h.

[0129] In the above technical scheme, a positive electrode active material containing both a layered structure and a spinel phase is prepared by sintering at a low temperature of 400°C to 480°C for 25h to 75h. The introduction of the spinel phase improves the stability of the layered structure, and the three-dimensional lithium ion diffusion channel improves the electrical conductivity of the layered material; and the layered structure makes up for the disadvantage of insufficient capacity of the spinel material to a certain extent.

[0130] Further optionally, in some embodiments of the present application, a hydroxide precursor is mixed with a lithium salt; and then the mixture is sintered at 401° C. to 479° C. for 25.5 h to 74.5 h.

[0131] Exemplarily, in some embodiments of the present application, a hydroxide precursor is mixed with a lithium salt; the mixture is then sintered at 401°C, 405°C, 410°C, 415°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C or in a range between any two of the foregoing values; and for 26h, 28h, 30h, 32h, 35h, 38h, 40h, 45h, 50h, 55h, 60h, 65h, 70h or in a range between any two of the foregoing values.

[0132] Furthermore, in some embodiments of the present application, the molar ratio of the Li element of the lithium salt to the Me element of the hydroxide precursor is 1.0 to 1.05.

[0133] In the above technical solution, the molar ratio of the Li element of the lithium salt to the Me element of the hydroxide precursor is 1.0 to 1.05. Within this range, it is further beneficial to improve the conductivity of the positive electrode active material and further beneficial to improve the rate performance of the positive electrode active material.

[0134] Further optionally, in some embodiments of the present application, the molar ratio of the Li element of the lithium salt to the Me element of the hydroxide precursor is 1.01 to 1.05.

[0135] Illustratively, in some embodiments of the present application, the molar ratio of the Li element of the lithium salt to the Me element of the hydroxide precursor is 1.01, 1.02, 1.03, 1.04, 1.05 or a range between any two of the foregoing values.

[0136] Further, in some embodiments of the present application, the mixture is sintered at 400° C. to 480° C. for 25 h to 75 h, comprising:

[0137] The temperature is raised from room temperature to 400°C to 480°C at a heating rate of 1°C / min to 3°C / min and sintered for 25h to 75h.

[0138] In the above technical solution, the above heating rate is advantageous for obtaining a positive electrode active material containing both a spinel phase and a layered structure.

[0139] Further optionally, in some embodiments of the present application, the mixture is sintered at 400° C. to 480° C. for 25 h to 75 h, comprising:

[0140] The temperature is raised from room temperature to 400°C to 480°C at a heating rate of 1.1°C / min to 2.9°C / min and sintered for 25h to 75h.

[0141] For example, in some embodiments of the present application, the mixture is sintered at 400° C. to 480° C. for 25 h to 75 h, comprising:

[0142] The temperature is raised from room temperature to 400°C-480°C at a heating rate of 1.2°C / min, 1.5°C / min, 1.8°C / min, 2.0°C / min, 2.2°C / min, 2.5°C / min or 2.8°C / min, and sintered for 25h-75h.

[0143] Furthermore, in some embodiments of the present application, the sintering atmosphere is air.

[0144] In the above technical solution, the above-mentioned air atmosphere sintering is adopted, which is conducive to obtaining a positive electrode active material containing both a spinel phase and a layered structure.

[0145] Furthermore, in some embodiments of the present application, the sintered material is washed with water;

[0146] The mass ratio of water to fuel is (15-30):1.

[0147] In the above technical solution, the sintered material is washed with water to remove the residual lithium, which is beneficial for obtaining a positive electrode active material with less impurities.

[0148] Further optionally, the mass ratio of the water to the fuel is 15:1, 18:1, 20:1, 25:1, 28:1, 30:1 or a range between any two of the aforementioned values.

[0149] Furthermore, the water washing time is 15 minutes to 30 minutes.

[0150] Within the above-mentioned water washing time range, the residual lithium can be effectively removed, which is beneficial for obtaining a positive electrode active material with less impurities.

[0151] Further optionally, the water washing time is 16 minutes to 29 minutes.

[0152] Illustratively, in some embodiments of the present application, the washing time is 16 min, 17 min, 18 min, 20 min, 22 min, 25 min, 28 min or a range between any two of the aforementioned values.

[0153] Furthermore, in some embodiments of the present application, the lithium salt includes one or more of lithium hydroxide, lithium carbonate, lithium acetate, lithium nitrate, lithium oxalate or lithium sulfate.

[0154] Further optionally, illustratively, in some embodiments of the present application, the method for preparing the positive electrode active material is carried out according to the following steps:

[0155] Step S1, putting the hydroxide precursor, lithium salt, and ball-milled zirconium beads into a drum-type ball mill mixer for mixing according to a ball-to-material mass ratio of 25-80, wherein the Li / Me molar ratio is 1.0-1.05, and Me is the total metal in the hydroxide precursor. Then the mixed material is put into a muffle furnace for sintering, the sintering temperature is 400°C-480°C, the heating rate is 1°C / min-3°C / min, the sintering time is 25-75h, and the sintering atmosphere is air. After sintering, the sintered material is mechanically ground and vibrated to obtain the sintered material.

[0156] Step S2, washing the burnt obtained in step S1 with water, the water-to-material mass ratio is (15-30):1, the washing time is 15-30 minutes, the washed burnt is filtered and transferred to a blast drying oven for drying at a temperature of 100°C for 10 hours. After drying, the burnt is mechanically ground and vibrated.

[0157] Some specific embodiments are listed below to better illustrate the present application.

[0158]

Preparation of positive electrode active materials

[0159] The hydroxide precursor, lithium salt and ball-milled zirconium beads are placed in a drum ball mill mixer for mixing at a ball-to-material mass ratio of 50, and the Li / Me molar ratio is controlled, where Me is the total metal in the hydroxide precursor. The mixed material is placed in a muffle furnace for sintering, and the sintering temperature and sintering time are controlled; the heating rate is 1°C / min, and the sintering atmosphere is air. The sintered material is mechanically ground and vibrated to obtain a sintered material.

[0160] The calcined material prepared above was washed with water, and the water-to-material ratio (mass ratio) and washing time were controlled. After the washed calcined material was filtered, it was transferred to a blast drying oven for drying at a temperature of 100°C for 10 hours. The dried calcined material was mechanically ground and vibrated to obtain the positive electrode active material.

[0161] The above hydroxide precursor can be obtained by purchasing a commercial precursor.

[0162] Example

[0163] A positive electrode active material is provided, which is prepared according to the above-mentioned preparation steps. The preparation process parameters of each embodiment are shown in Table 1; various performance parameters of the prepared positive electrode active material are tested, and the results are shown in Tables 1 and 2.

[0164] Comparative Example 1

[0165] Provided is a positive electrode active material, which is an undoped positive electrode active material, and its chemical formula is: LiNi 0.5 Mn 0.5 O2.

[0166] The positive electrode active material can be obtained by purchasing from the market.

[0167] Comparative Example 2

[0168] Provided is a positive electrode active material, which is a positive electrode active material with a pure layered structure. Chemical formula: LiNi 0.4 Mn 0.4 La 0.2 O2.

[0169] Comparative Example 3

[0170] Provides a positive electrode active material, which is a pure spinel positive electrode material, chemical formula: LiNi 0.5 Mn 1.5 O4.

[0171] Comparative Example 4

[0172] A positive electrode active material is provided, and the preparation process is as follows:

[0173] 1) Preparation of nickel-cobalt-manganese precursor Ni by hydroxide coprecipitation method 0.5 Co0.2 Mn 0.3 (OH)2;

[0174] 2) Ni-Co-Mn precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2 was mixed with Li2CO3 and the additive ZrO2 to make the molar ratio of Li / Me be 0.95, Me was the total amount of transition metal in the nickel-cobalt-manganese precursor, the amount of ZrO2 added was 4000ppm, and the material was heated under air flow of 8m 3 / h box furnace and the temperature was 1000℃, the first sintering was carried out for 10h, and then the temperature was lowered to 250℃ and kept for 4h to obtain the lithium-deficient positive electrode material Li δ Ni 0.5 Co 0.2 Mn 0.3 O2(0.5≤δ<1);

[0175] 3) Li-deficient cathode material Li δ Ni 0.5 Co 0.2 Mn 0.3 O2 was crushed and then mixed with TiO2 and Li2CO3 to make the molar ratio of Li / Me be 1.07, Me is the total amount of transition metal in the lithium-deficient positive electrode material, the amount of TiO2 added was 500ppm, and the material was heated under air flow of 6m 3 / h box furnace and a second sintering at a temperature of 600°C for 7h, and then crushing and screening to obtain a layered-spinel phase composite positive electrode material.

[0176]

Preparation of positive electrode

[0177] The positive electrode active materials prepared in the above-mentioned embodiments or comparative examples are used to prepare positive electrode sheets.

[0178] The positive electrode active material was put into a 5L stirring tank for premixing for 30 minutes, and then the conductive agent acetylene black (SP) and the binder polyvinylidene fluoride (PVDF) were added for secondary dry mixing for 30 minutes. Finally, the solvent N-methylpyrrolidone (NMP) was added and stirred rapidly under vacuum to form a slurry. Among them, the mass ratio of positive electrode active material: acetylene black: polyvinylidene fluoride = 96:2:2, and the solid content of the slurry is 70wt.%. The slurry was evenly coated on both sides of an aluminum foil with a thickness of 12μm, and the coated pole piece was taken out after drying in an oven at 100-130℃ for half an hour. Among them, the positive electrode active material loading of the pole piece is 21.5mg / cm 2 .

[0179]

Preparation of negative electrode sheet

[0180] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carbon methyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system in a weight ratio of 90:5:2:2:1, and then coated on a copper foil, dried, and cold pressed to obtain a negative electrode sheet.

[0181]

Battery preparation

[0182] A polyethylene porous polymer film is used as an isolation film. The positive electrode sheet, isolation film, and negative electrode sheet prepared above are stacked in order, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell. The bare cell is placed in an outer package, and the prepared basic electrolyte, i.e., 1 mol / L LiPF6 / (EC+EMC+DMC) (volume ratio of 1:1:1) is injected, and encapsulated to obtain a full battery.

[0183] The battery performance was tested and the test results are shown in Table 2.

[0184]

Performance test method

[0185] (1) XRD:

[0186] The positive electrode active material of each embodiment or comparative example was tested by XRD diffraction pattern.

[0187] The diffraction angle (2θ1) of the first main diffraction peak, the diffraction angle (2θ2) of the second main diffraction peak, and the ratio (I1 / I2) of the intensity of the first main diffraction peak to the intensity of the second main diffraction peak are determined according to the XRD diffraction pattern.

[0188] (2) Dislocation density:

[0189] The XRD diffraction pattern in (1) above is used to characterize the dislocation density of the positive electrode active material.

[0190] Dislocation density β = (1 / D) 2 ×10 16 , where D = K λ / Bcosθ, K=0.9, λ=1.5406, B is the half-height width of the crystal plane of the positive electrode active material (hkl) in the XRD diffraction pattern, and θ is the diffraction angle.

[0191] (3) Micro stress:

[0192] The XRD diffraction pattern in (1) above is used to characterize the micro stress of the positive electrode active material.

[0193] Micro stress = (βhkl × Cosθhkl) / (4sinθhkl), where θhkl is the diffraction angle of the positive electrode material (hkl) crystal plane in the XRD diffraction pattern, and βhkl is the half-height width of the positive electrode material (hkl) crystal plane in the XRD diffraction pattern.

[0194] (4) Material Span:

[0195] Refer to GB / T 19077-2016 / ISO 13320:2009 particle size distribution laser diffraction method, using Malvern 3000 equipment for measurement, Span = (D v90 -D v10 ) / D v50 .

[0196] (5) BET:

[0197] The specific surface area BET refers to the total area per unit mass of a material. The specific surface area of ​​a positive electrode active material can be obtained by conventional testing methods, for example, by referring to the national standard GBT 19587-2004.

[0198] The BET test method before and after washing in Table 1 is the same. Unit: (m 2 / g)

[0199] (6) Battery cell cycle retention rate (%)

[0200] Take the whole battery cell as the test object, in a constant temperature environment of 25℃, at a voltage of 2.5V~4.55V, charge to 4.55V at a rate of 1C, then charge at a constant voltage at 4.45V to a current ≤0.05mA, let it stand for 5 minutes, and then discharge to 2.5V at a rate of 1C, record the discharge energy, repeat the previous process, and obtain the capacity retention rate after the specified number of cycles, capacity retention rate = first cycle discharge energy / discharge energy at the specified number of cycles × 100%, the number of cycles tested this time is 100.

[0201] (7) Testing method for measuring storage performance of battery cells:

[0202] At a constant temperature of 25°C, let it stand for 5 minutes, discharge to 2.5V at 1 / 3C, let it stand for 5 minutes, charge to 4.46V at 1 / 3C, then charge at 4.46V at a constant voltage until the current is ≤0.05mA, let it stand for 5 minutes, the charging capacity at this time is recorded as C0, then discharge to 2.5V at 1 / 3C, the discharge capacity at this time is the initial gram capacity, recorded as D0; then charge the battery to 4.5V at a constant current of 0.33C and charge at a constant voltage until the current is ≤0.05mA, let it stand for 5 minutes, and finally put it in a high and low temperature box at 60°C, let it stand for 1 hour until the battery temperature reaches the target temperature and then store it; take it out after 15 days, repeat the previous process at a constant temperature of 25°C, and record the capacity D every 15 days n (n=0,1,2……), calculate the capacity retention rate after 60 days of storage: (D4-D0) / D0*100%.

[0203] (8) Battery capacity detection:

[0204] In a constant temperature environment of 25℃, let it stand for 30 minutes, discharge to 2.5V at 0.1C, let it stand for 5 minutes, charge to 4.65V at 0.1C, then charge at constant voltage at 4.65V to a current ≤0.05mA, let it stand for 5 minutes, then discharge to 2.5V at 0.1C. The discharge capacity at this time is the initial gram capacity.

[0205] (9) Battery rate performance test: At a constant temperature of 25°C, let it stand for 30 minutes, discharge to 2.5V at 0.1C, let it stand for 5 minutes, charge to 4.65V at 0.1C, then charge at 4.65V at constant voltage until the current is ≤0.05mA, let it stand for 5 minutes, then discharge to 2.5V at 0.1C. The discharge capacity at this time is recorded as C0: let it stand for 30 minutes, charge to 4.65V at 0.5C, then charge at 4.65V at constant voltage until the current is ≤0.05mA, let it stand for 5 minutes, then discharge to 2.5V at 0.5C. The discharge capacity at this time is recorded as C1. Rate performance = C0 / C1*100%.

[0206] (10) Charge and discharge curve

[0207] In a constant temperature environment of 25℃, let it stand for 30 minutes, discharge to 2.5V at 0.1C, let it stand for 5 minutes, charge to 4.65V at 0.1C, then charge at constant voltage at 4.65V to a current ≤0.05mA, let it stand for 5 minutes, and then discharge to 2.5V at 0.1C.

[0208] Table 1

[0209]

[0210] Table 2

[0211]

[0212]

[0213] From the above table data and the attached drawings of the specification, it can be seen that:

[0214] Compared with Comparative Examples 1 to 4, the rate performance of the above-mentioned embodiments is improved.

[0215] Furthermore, Comparative Example 2 is a positive electrode material with a pure layered structure. Compared with Example 1, it can be seen that the positive electrode active material of Example 1 has effectively improved battery capacity, cycle performance, storage performance and rate performance relative to the positive electrode material with a pure layered structure of Comparative Example 2.

[0216] Furthermore, Comparative Example 3 is a pure spinel positive electrode material. Compared with Example 1, it can be seen that the positive electrode active material obtained in Example 1 has effectively improved battery capacity, cycle performance, storage performance and rate performance relative to the pure spinel positive electrode material of Comparative Example 3.

[0217] Furthermore, the sintering temperature of Comparative Example 4 is too high. The material obtained in Comparative Example 4 is prepared by first sintering at high temperature to obtain a lithium-deficient material and then supplementing lithium. The material no longer has the characteristics of a spinel structure and is more inclined to a layered structure; its I1 / I2 value is much larger than the I1 / I2 of the above-mentioned embodiments.

[0218] Furthermore, it can be seen from Table 2 that the positive electrode active material obtained in Example 1 has effectively improved battery capacity, cycle performance, storage performance and rate performance compared to the positive electrode material of Comparative Example 4.

[0219] Further, from the attached manual Figure 6 It can be seen that Examples 1-3 show charge and discharge curves of spinel and layered structure materials, respectively; while Comparative Examples 2 and Comparative Examples 4 have no spinel discharge platform at 2.5V-3.0V, showing charge and discharge curves of a single layered structured positive electrode material.

[0220] Furthermore, compared with Example 1, Comparative Example 1 is an undoped positive electrode material. It can be seen that the battery capacity of the positive electrode active material obtained in Example 1 is effectively improved; the cycle performance is effectively improved; the storage performance is effectively improved; and the rate performance is effectively improved.

[0221] Furthermore, compared with Example 1, Example 12 is an unwashed material. It can be seen that the battery capacity, cycle performance, storage performance, and rate performance of the positive electrode active material of Example 1 are better.

[0222] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

Claims

1. A positive electrode active material, characterized in that: The chemical formula of the positive electrode active material is: Li a Ni b Mn c M d O2, wherein 1≤a≤1.05, 0.22≤b≤0.5, 0.47≤c≤0.75, 0.01≤d≤0.03, and M includes at least one of Mg, Nb, Cr, Ce, Fe, La, Ta, Al, V, Ti, Zr, Sn, Mo or Co; the XRD spectrum of the positive electrode active material includes a first main diffraction peak and a second main diffraction peak; the diffraction angle of the first main diffraction peak is 16°~19°; the diffraction angle of the second main diffraction peak is 42°~45°.

2. The positive electrode active material according to claim 1, characterized in that The ratio of the intensity of the first main diffraction peak to the intensity of the second main diffraction peak is 0.8 to 2.0; optionally, the ratio of the intensity of the first main diffraction peak to the intensity of the second main diffraction peak is 0.81 to 1.

99.

3. The positive electrode active material according to any one of claims 1 to 2, characterized in that: The specific surface area of ​​the positive electrode active material after washing is less than 8 m 2 / g; Optionally, the specific surface area of ​​the positive electrode active material after washing is greater than 2m 2 / g and less than 8m 2 / g.

4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The dislocation density of the positive electrode active material is 1.0*10 13 ~2.5*10 13 ; Optionally, the dislocation density of the positive electrode active material is 1.1*10 13 ~2.4*10 13 .

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The micro stress of the positive electrode active material is less than or equal to 1.2%. Optionally, the micro stress of the positive electrode active material is 0.1% to 0.5%.

6. The positive electrode active material according to any one of claims 1 to 5, characterized in that: The material diameter distance of the positive electrode active material is greater than 1.2; optionally, the material diameter distance of the positive electrode active material is greater than 1.2 and less than 1.

5.

7. The method for preparing a positive electrode active material according to any one of claims 1 to 6, characterized in that: include: Sintering a mixture of a hydroxide precursor and a lithium salt; the total metal in the hydroxide precursor is Me, and Me includes nickel, manganese and M.

8. The method for preparing a positive electrode active material according to claim 7, characterized in that: The sintering comprises: sintering the mixture at 400° C. to 480° C. for 25 h to 75 h.

9. The method for preparing a positive electrode active material according to any one of claims 7 to 8, characterized in that: The molar ratio of the Li element of the lithium salt to the Me element of the hydroxide precursor is 1.0 to 1.

05.

10. The method for preparing a positive electrode active material according to any one of claims 7 to 9, characterized in that: The method further comprises: washing the sintered material obtained by sintering; The mass ratio of water to the burning material is (15-30):1; optionally, the water washing time is 15min-30min.

11. A positive electrode sheet, characterized in that: The positive electrode plate comprises the positive electrode active material according to any one of claims 1 to 6; or the positive electrode plate comprises the positive electrode active material prepared by the method for preparing the positive electrode active material according to any one of claims 7 to 10.

12. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 11.

13. An electrical equipment, characterized in that: The electrical device comprises the battery according to claim 12.

Citation Information

Patent Citations

  • Electrochemical device and electronic device

    CN115053379A

  • Positive electrode active material, positive electrode plate and sodium ion battery

    CN115472818A

  • Positive electrode material and positive plate and battery comprising positive electrode material

    CN115863604A